THE EFFECT OF COMPENSATION, WORK DISCIPLINE, AND MOTIVATION ON EMPLOYEES’ WORK PRODUCTIVITY - Burhanudin; Risman Hariwibowo; Muhammad Miftahuddin (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This research aims to examine the influence of compensation on employee work productivity, to investigate the impact of work discipline on employee work productivity, and to assess the effect of motivation on employee work productivity.  The participants in this study consisted of 43 employees from PT.  Titipan Ilahi located in Denpasar, Bali. Data were collected using a questionnaire and analyzed using multiple linear regression. The research findings reveal that:  (1) compensation significantly influences employee work productivity; (2) work discipline does not significantly affect employee work productivity; and (3) motivation significantly affects employee work productivity